2019
DOI: 10.1021/acs.langmuir.9b01218
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Interfacial Interactions in Dodecane/Brine Pickering Emulsions Stabilized by the Combination of Cellulose Nanocrystals and Emulsifiers

Abstract: Interfacial properties of cellulose nanocrystals (CNC) and surfactants were studied in high ionic strength (I) brines and correlated to the stability of dodecane/brine Pickering emulsions. Bis-(2-hydroxyethyl) cocoalkylamine (CAA), dodecyltrimethylammonium bromide (DTAB), and octyl-β-d-glucopyranoside (OGP) were adsorbed onto CNC in American Petroleum Institute (API) brine (I = 1.9 M) and synthetic seawater (SSW), with I = 0.65 M. Raman spectroscopy indicated that hydroxyl groups on the CNC surface interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…This result was surprising since the adsorption onto the CNC surface was expected to drive DTAB away from the interface and increase its γ ow . Previous surface tension measurements in the air indicated a critical micelle concentration (CMC) of DTAB in API brine of 0.16 ± 0.03 g/L, thus at the 0.45 g/L used herein, adsorption onto CNC likely removed surfactant from micelles instead of the interface . The same concentration was used for the heptane/brine interface; however, we speculate that heptane may shift the CMC to a higher concentration due to having a polarity closer to the linear alkyl chain of DTAB, compared to the more hydrophobic PFO.…”
Section: Results and Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This result was surprising since the adsorption onto the CNC surface was expected to drive DTAB away from the interface and increase its γ ow . Previous surface tension measurements in the air indicated a critical micelle concentration (CMC) of DTAB in API brine of 0.16 ± 0.03 g/L, thus at the 0.45 g/L used herein, adsorption onto CNC likely removed surfactant from micelles instead of the interface . The same concentration was used for the heptane/brine interface; however, we speculate that heptane may shift the CMC to a higher concentration due to having a polarity closer to the linear alkyl chain of DTAB, compared to the more hydrophobic PFO.…”
Section: Results and Discussionmentioning
confidence: 72%
“…CNC and CNC + DTAB conjugates in high ionic strength brine ( I = 1.9 M) have their surface charge screened due to the collapse of the electric double layer causing them to aggregate. This results in the formation of CNC and CNC + DTAB networks contributing to increased viscosity of the aqueous phase and thereby forming stable gel-like emulsions. ,, A previous study with dodecane/brine emulsions indicated that adsorption of DTAB onto the surface of CNC aggregates increased their hydrophobicity, thus facilitating the migration of CNC onto the oil–water interface. , However, this does not appear to be enough to stabilize PFO/brine interfaces (Supporting Information, Figure S3).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the fluids showed elevated electrical stability values ( Table 2 ). Probably, the amount of modified cellulose nanocrystals was not enough to result in a substantial difference in the electrical stability [ 31 ].…”
Section: Resultsmentioning
confidence: 99%